Manutenção centrada em confiabilidade: estudo de caso da eficácia dos equipamentos industriais - Marques, Gabriel Rezende (2017)
Most industrial machines operate from motors, which are susceptible to defects and failures during use. These problems can cause machine shutdown and loss of efficiency in the production process. Therefore, it is very important that the maintenance service knows the equipment of their responsibility and know the conditions of effectiveness of each one, So that it can effectively carry out the necessary and timely intervention so that production is not abruptly and inadvertently interrupted. The concept of predictive maintenance based on reliability is gaining prominence in the present day, consisting of the scheduled maintenance based on the diagnosis of the conditions of the equipment, avoiding unexpected stops. In the work carried out, a qualitative research methodology was used, with a bibliographical study enriched with a case study employing maintenance techniques centered on reliability. To reduce or eliminate problems generated in the operation of equipment, it was necessary to use maintenance techniques to predict failures before they occur. Therefore, the behavior of these equipment during their life cycle is evaluated, through a predictive maintenance technique associated to the knowledge of the machine and the reliability of the maintenance service. A table was drawn up to classify the criticality of the equipment and favor the prioritization of maintenance in critical components for the company. The equipment considered critical was subjected to vibration analysis to predict failures and to prevent machine shutdown. Through this work, it was possible to demonstrate that the maintenance centered on reliability aims at the efficiency of the equipment and the proper functioning of any organization. In addition, it has been concluded that vibration analysis is an efficient and important tool for predictive maintenance.